Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper for Chile describes the postcrisis recovery experience. The recovery from the 2008-2009 global crisis has been markedly different both among advanced and emerging economies. The steady improvement in the labor wedge-distortions related to the consumption leisure decision helped support the recovery. In Chile, the growth generated by this improvement, was sufficient to overcome the relatively weak performance of efficiency (TFP). Chile's recovery has been characterized by strong investment growth, 0.8 percentage points higher than the precrisis trend. The establishment of the Financial Stability Council in 2011 is an important step to ensure close coordination among the institutions involved in Chile's financial prudential framework.